Development of graphite foam infiltrated with MgCl2 for a latent heat based thermal energy storage (LHTES) system. (August 2016) - Singh, Dileep; Kim, Taeil; Zhao, Weihuan; Yu, Wenhua; France, David M.
Abstract: Thermal energy storage (TES) systems that are compatible with high temperature power cycles for concentrating solar power (CSP) require high temperature media for transporting and storing thermal energy. To that end, TES systems have been proposed based on the latent heat of fusion of the phase change materials (PCMs). However, PCMs have relatively low thermal conductivities. In this paper, use of high-thermal-conductivity graphite foam infiltrated with a PCM (MgCl2 ) has been investigated as a potential TES system. Graphite foams with two porosities were infiltrated with MgCl2 . The infiltrated composites were evaluated for density, heat of fusion, melting/freezing temperatures, and thermal diffusivities. Estimated thermal conductivities of MgCl2 /graphite foam composites were significantly higher than those of MgCl2 alone over the measured temperature range. Furthermore, heat of fusion, melting/freezing temperatures, and densities showed comparable values to those of pure MgCl2 . Results of this study indicate that MgCl2 /graphite foam composites show promise as storage media for a latent heat thermal energy storage system for CSP applications. Highlights: Graphite foam was infiltrated with a phase change material (MgCl2 ) to almost full capacity. Heat of fusion, melting/freezing temperature, and thermal diffusivity of MgCl2 /graphite foam composites were measured. Measured heat of fusion of compositeswere proportional to the mass fraction of MgCl2 in the composite. The estimated thermal conductivities of MgCl2 /graphite foam composites were significantly higher than that of pure MgCl2 . MgCl2 /graphite foam composites have been demonstrated for use for latent heat thermal energy storage system for concentrated solar power.